Methicillin-resistant staphylococcus aureus infections in collegiate football players - Bowers, A. L.; Huffman, G. R.; Sennett, B. J. (Medicine & Science in Sports & Exercise, 2008)
Abstract: Purpose: Methicillin-resistant Staphylococcus aureus (MRSA) has been recognized as a serious skin infection in the athletic population. Literature in reference to football players has been sparse. We sought to better elucidate circumstances surrounding such infections in collegiate football players.